1990
DOI: 10.1111/j.1476-5381.1990.tb14719.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of GABAB‐receptor‐mediated responses in the guinea‐pig isolated ileum and vas deferens by phosphono‐analogues of GABA

Abstract: 1 The phosphono-analogues of y-aminobutyric acid (GABA), 4-amino-butylphosphonic acid (4-ABPA), 3-amino-2(4-chlorophenyl)-propylphosphonic acid (phaclofen) and 3-amino-2-cyclohexylpropylphosphonic acid, each antagonized the GABA-and baclofen-induced GABAB-receptor-mediated depression of twitch responses to transmural stimulation in the guinea-pig isolated ileum, in a concentration-dependent, reversible and surmountable manner (apparent pA2 = 4.0 + 0.1, 4 + 0.2 and 3.7 + 0.2 respectively, compared with 3.9 + 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In addition, we have confirmed that the more potent antagonist 2-OH-saclofen is effective against baclofen at the crayfish GABA B receptors, as was originally shown by Fischer and Parnas (1996a). In particular, we have established the concentration-dependent depression of excitatory transmitter release by baclofen at the crayfish opener neuromuscular system, with an EC 50 value of 30 M and a maximum depression of 87% at 150 M. We made two different estimates of potency for phaclofen as an antagonist at the crustacean GABA B receptors, both of which gave a mean value of pA 2 ϭ 4.3, close to the pA 2 value of 4.0 previously obtained for phaclofen in the mammal (Kerr et al 1990). In addition, we found that the phosphonic analogue of GABA, 3-APPA, itself partly reduced transmitter release, yet attenuated the action of baclofen when coapplied.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, we have confirmed that the more potent antagonist 2-OH-saclofen is effective against baclofen at the crayfish GABA B receptors, as was originally shown by Fischer and Parnas (1996a). In particular, we have established the concentration-dependent depression of excitatory transmitter release by baclofen at the crayfish opener neuromuscular system, with an EC 50 value of 30 M and a maximum depression of 87% at 150 M. We made two different estimates of potency for phaclofen as an antagonist at the crustacean GABA B receptors, both of which gave a mean value of pA 2 ϭ 4.3, close to the pA 2 value of 4.0 previously obtained for phaclofen in the mammal (Kerr et al 1990). In addition, we found that the phosphonic analogue of GABA, 3-APPA, itself partly reduced transmitter release, yet attenuated the action of baclofen when coapplied.…”
Section: Discussionsupporting
confidence: 63%
“…The vas deferens was stimulated transmurally using a Grass S48 stimulator with 1 s trains of pulses of 0.5 ms width, 70 V amplitude at 20 Hz, repeated at 25 s intervals (Ellis & Burnstock, 1989). The ileum was stimulated transmurally using a Scientific and Research Instrument Ltd. (U.K.) stimulator with 0.1 ms pulses, 10 V amplitude at a frequency of 0.1 Hz (Kerr et al, 1990). Cumulative concentration-response curves to agonist alone were constructed, allowing 5 min between each addition of drug.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…These were transmurally stimulated, with trains of rectangular pulses at 0.04Hz. Each train was of Is duration consisting of 20 pulses of 0.5ms pulse width, 70V stimulation amplitude (adapted from Kerr et al, 1990). Cumulative concentration-response curves were constructed.…”
Section: Concmentioning
confidence: 99%